Mispricing pada Akrual Abnormal (Studi Empiris pada Bursa Efek Jakarta) - Evi Gantyowati; Solichah Ratnawati (Jurnal Akuntansi dan Bisnis, 2004)
This research aims to test mispricing abnormal accrual on Jakarta Stock Exchange. It bases on Xie’s test (2001). Sample collecting method is purposive sampling. There are 42 manufacture enterprises as samples which match the criteria stated. The research uses industries model to estimate normal accrual. The Result shows that there is mispricing abnormal accrual.